Review: The diversity of local cattle in Indonesia and the efforts to develop superior indigenous cattle breeds (Biodiversitas Journal of Biological Diversity, 2016)
Sutarno, Setyawan AD. 2016. The diversity of local cattle in Indonesia and the efforts to develop superior indigenous cattle breeds. Biodiversitas 16: 275-295. Cattle breeding are regarded indigenous to Indonesia. In the country, there are three types of cattle breeds: zebu (Bos indicus),Â Bali cattle (Bos javanicus),Â and taurine (Bos taurus). These breeds are farmed for their meat, milk, leather, and their power for agricultural work. Zebu was introduced by the Indians in the beginning of the first century. Bali cattle are indigenous breeds that have been domesticated from wild bantengs (Bos javanicus) in Java and Bali for hundreds of years. Several breeds of taurine were imported in early eighteenth century to be used as dairy cattle. Zebu and taurine are the major cattle breeds of the world; whereas in Indonesia, the major cattle breeds are Bali cattle, Ongole crossbred, and Madura cattle, which is a crossbred of the former two. Primary breeding between species in the genus Bos will result in sterile male and fertile female offspring. However, secondary breedingÂ with a crossbred female will result in fertile offspring. In Indonesia, there are several local cattle breeds of zebu that have adapted to the local condition, for example Ongole crossbred, Aceh cattle, Pesisir cattle, Sumba Ongole, and, the less commonly found, Galekan cattle of Trenggalek. In addition, there are many hybrids between zebu and Bali cattle such as Madura cattle, Jabres cattle of Brebes, Rancah cattle of Ciamis, and Rambon cattle of Bondowoso, Banyuwangi, and the surrounding areas. A crossbreeding of zebu and taurine produces Grati dairy cattle. In 1970s, an Artificial Insemination program was conducted in a large scale using male cattle and semen from several breeds of zebu (Brahman, Brahman Cross)Â and taurine (particularly Simmental, Limousin, Holstein Friesians). The program resulted in more complex genetic mixes. Crossbreeding conducted directly in the field causes a concern since it may threaten the purity of the native species and decrease the cattleâ€™s potential for adaptation, reproduction, and productivity. It is better to conductÂ crossbreeding programs privately in research centers or corporate/large farmers, of which the result can be distributed to smaller farms. â€œOngolizationâ€ program that was introduced in the early twentieth century should be a lesson to learn, because it had led to the extinction of Javanese cattle, while the produced offspring, the Ongole Crossbred, are considered unsatisfactory so that they still have to be crossbred with other species of cattle, particularly taurine.